Pemberdayaan Perempuan Dalam Pelatihan Pengurusan Jenazah Melalui Metode Demonstrasi Di Kelurahan Tasikmadu Kota Malang - Fitriani, Laily; Munjiah, Ma’rifah; Muassomah, Muassomah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Community empowerment as part of activities that are continuously socialized by the government receives very good attention, especially in empowering women. Many efforts have been made by various parties to make this woman empowered, including in the management of bodies where the general public considers that the management of corpse is only a modin task. This study aims to find out how the initial conditions of women in the management of corpse in the Tasikmadu village in Malang and how the process of empowering women and the changes that occur in the management of corpse through demonstration methods in the Tasikmadu village of Malang. This research is a participatory action research (PAR) using the method proposed by Kurt Lewin based on four main components, namely: planning, action, observation and reflection. The results of the study explained that the initial conditions of women in the Tasikmadu village were quite powerful but for empowerment in the management of the remains was minimal, due to the modin as the person in charge of the management of the corpse and the lack of knowledge and skills in the management of the corpse. While the training process uses the demonstration method, which is a method that is carried out by providing direct media, so participants can gain theoretical and practical experience. In the initial cycle, participants explored the theoretical side of corporeal materials in accordance with the Shari'a and corporeal materials. In the second cycle the participants gained firsthand experience to practice the material that had been obtained by the resource persons through puppet media about how to care for the body when experiencing death, bathing, believing, and soliciting to bury the bodies in groups.